The role of intrapreneurs in driving entrepreneurial transformation in Universities: A bibliographic analysis between 1990 and 2024 - Orsolya Gabriella Gregán; Sándor Kovács; Zoltán Gabnai (Administrative Sciences, 2024)
Prior research has demonstrated the value of an entrepreneurial mindset in business. The so called third mission is also becoming an increasingly important aspect of university operations. This involves leveraging knowledge generated at the university level to create close links with society and the economy. The role of intrapreneurs has been examined in the corporate, for-profit sector. However, these agents of change also play a significant role in the advancement of entrepreneurial universities. The present research investigates the role of intrapreneurs in entrepreneurial universities through a bibliographic analysis using RStudio biblioshiny on the Scopus and Web of Science databases. It is evident that the literature on this subject has gained interest in recent years, yet the number of documents remains limited, with a small number of authors publishing them. The development of keywords is also notable, including the emergence of sustainability, which is linked to intrapreneurs and the entrepreneurial universities. Although this study has its limitations, it can show how and where authors should publish, what the basic and the emerging topics are, what the most important keywords are and how these are connected and how countries cooperate in searching for solutions in this globally recognized research area.
Keywords: 350; bibliographic analysis; biblioshiny; intrapreneurship; entrepreneurial university; sustainability; innovation; education